Evidence human FTO catalyses hydroxylation of N6-methyladenosine without direct formation of a demethylated product contrasting with ALKBH5/2/3 and bacterial AlkB - Simranjeet, K.; Pratheesh, M.; Samanpreet, K.; Yingqi, L.; Eidarus, S.; Dong, Z.; Shifali, S.; Christopher, J.S.; Wei Shen, A. (Oxford University Press, 2025)
N6-Methyladenosine (m6A) is a prevalent post-transcriptional modification in eukaryotic messenger RNA. Two cancer-linked human Fe(II) and 2-oxoglutarate (2OG)-dependent oxygenases, the fat mass and obesity associated-protein (FTO), and AlkB human homolog 5 (ALKBH5) catalyse m6A methyl group oxidation. While ALKBH5 has consistently been reported to catalyse m6A demethylation, there are conflicting reports con- cerning the FTO products. We report studies using mass spectrometry and nuclear magnetic resonance comparing products of FTO, ALKBH5, and DNA damage repair demethylases (human ALKBH2 and ALKBH3 and bacterial AlkB, using m1A single-stranded DNA substrates). The results with m6A-containing single-stranded RNA (ssRNA) and N6,2 -O-dimethyladenosine adjacent to the 5 m7G triphosphate cap ssRNA substrates imply that the predominant FTO product is N6-hydroxymethyladenosine, either with or without methylation on the substrate ribose 2 -hydroxyl group. The nascent hemiaminal product undergoes relatively slow non-enzyme catalysed fragmentation giving adenosine/formaldehyde. The other four 2OG-dependent oxygenases tested, including ALKBH5, produce demethylated bases as the predominant products. The results imply that, at least in isolated form, FTO preferentially acts as a hydroxylase, producing a hemiaminal product, rather than a demethylase, distinguishing it from ALKBH5. They highlight a need for investigations into the roles of hemiaminal-type modifications to nucleic acids, in both healthy biology and disease.